2020
DOI: 10.1002/ajmg.a.61742
|View full text |Cite
|
Sign up to set email alerts
|

49,XXXXYsyndrome: A study of neurological function in this uncommon X and Y chromosomal disorder

Abstract: 49,XXXXY is a rare chromosomal variation characterized by deficits in motor, language, and cognitive domains. This study reports on the neurological function and dysmorphic features in the largest cohort to date. Seventy-two boys with 49,XXXXY were evaluated on a variety of domains including a neurological examination and neuromotor assessments including the Beery Buktenica Developmental Test of Visual-Motor Integration, Sixth Edition, the Bayley Scales of Infant and Toddler Development, Third Edition (BSID-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…They show specific dysmorphic features, organ anomalies, severe mental retardation and congenital malformation, which can lead to a diagnosis in the first year of life. [ 18 ]. Some authors hypothesised that the overall features of affected patients were due to the abnormal dosage of genes beyond what is normally guaranteed between males and females by X-inactivation of the second X chromosome in females [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They show specific dysmorphic features, organ anomalies, severe mental retardation and congenital malformation, which can lead to a diagnosis in the first year of life. [ 18 ]. Some authors hypothesised that the overall features of affected patients were due to the abnormal dosage of genes beyond what is normally guaranteed between males and females by X-inactivation of the second X chromosome in females [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common physical and clinical features of 49, XXXXY subjects include facial dysmorphisms (upslanting palpebral fissures in 100 % of cases, arched eyebrows, ocular hypertelorism, synophrys, flat nasal bridge, frontal bossing, low-set ears), cardiac defects, endocrinologic abnormalities (e.g., hypogonadism, hypogenitalism, growth retardation), microcephaly, short stature, multiple skeletal anomalies, mental retardation and speech delay [ 10 , 15 , 18 ]. Other features were less frequently observed and consisted of alterations in muscular tone (generalised hypotonia), joint laxity, cleft palate, bifid uvula, kidney and ear malformations, and other skeletal anomalies (such as plagiocephaly, pectus excavatum, pes cavus, radioulnar synostosis, fifth finger clinodactyly, syndactyly and genu valgum) [ 10 , 15 , 18 ]. In 2019, Burgemeister et al [ 15 ] focused on dental anomalies that can occur throughout life, such as delayed dentition and eruption, hypodontia and malocclusion [ 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samango‐Sprouse et al (2020) expanded on the dysmorphological and neurological profiles of males with 49,XXXXY. Several novel facial features are reported, including a smooth philtrum (29.17%), low hanging columnella (57.9%) and dystopia canthorum (42.86%).…”
Section: Infancy Toddlers School‐aged Adolescence Managementmentioning
confidence: 99%
“…Neurocognition in boys with 49,XXXXY may also be influenced by testosterone replacement therapy. Several research studies have indicated the restorative impact of hormonal replacement on the neurodevelopmental phenotype of boys with 49,XXXXY, including speech and language and motor development (Samango‐Sprouse et al, 2020; Samango‐Sprouse et al, 2020; Galasso, Arpino, Fabbri, & Curatolo, 2003; Linden et al, 1995; Mazzilli et al, 2016). However, research regarding the influence of the administration of testosteronne on the neurocognitive profile of 49,XXXXY is limited.…”
Section: Introductionmentioning
confidence: 99%